The geopolitical case for CMU and two different pathways toward capital market integration - Florian Heider; Jan Pieter Krahnen; Katja Langenbucher; Vincent Lindner; Jonas Schlegel; Tobias Tröger (Leibniz Institute for Financial Research SAFE, 2024)
Almost ten years after the European Commission action plan on building a capital markets union (CMU) and despite incremental progress, e.g. in the form of the EU Listing Act, the picture looks dire. Stock exchanges, securities markets, and supervisory authorities remain largely national, and, in many cases, European companies have decided to exclusively list overseas. Notwithstanding the economic and financial benefits of market integration, CMU has become a geopolitical necessity. A unified capital market can bolster resilience, strategic autonomy, and economic sovereignty, reduce dependence on external funding, and may foster economic cooperation between member states. The reason for the persistent stand-still in Europe's CMU development is not so much the conflict between market- and state-based integration, but rather the hesitancy of national regulatory and supervisory bodies to relinquish powers. If EU member states wanted to get real about CMU (as they say, and as they should), they need to openly accept the loss of sovereignty that follows from a true unified capital market. Building on economic as well as historical evidence, the paper offers viable proposals on how to design competent institutions within the current European framework. This note outlines the case for speedy capital market integration and for the adoption of a common regulatory framework and single supervisory authority from a political economy perspective. We also show the alternative case for harmonization and centralization via regulatory competition, elaborating how competition between EU jurisdictions by way of full mutual recognition may lead to a (cost-)efficient and standardized legal framework for capital markets. Lastly, the note addresses the political economy conflict that underpins the implementation of both models for integrating capital markets. We point out that, in both cases, national authorities experience a loss of legislative and jurisdictional competence at the national level. We predict that any plan to foster a stronger capital market union, following an institution based or a market-based strategy, will face opposition from powerful national stakeholders.
urn:nbn:de:hebis:30:3-700108
Keywords: 330; Capital Markets Union; Capital Markets; Regulatory Arbitrage; European Integration; Institution-building; Geopolitics